PERAN United State Agency International Development (USAID) DALAM KONSERVASI LAUT DI KEPULAUAN ANAMBAS, KEPULAUAN RIAU - Nilam Sari; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This is a study about the role of United Nation Agency International Developtment in marine conservation Anambas Island, Riau Island Province. USAID is United Nation’s federal agencies that assist to other countries on the event of democracy, enverionment, gender, education etc. USAID has been engaged in marine conservation development in Anambas Island.This script uses the conceptual base with the concept of international cooperation where in USAID and Anambas become the focus of study. It is also supported by the range or nation-state, pluralism perspective and Green theory. The concept directs to the qualitative methode and literature study as the resource of the information.The role performed by USAID were give a fund grant to Indonesia, cooperation with Indonesia’s MPAG and zoning or mapping conservation ragion in Anambas Island, Riau Island Province.Keyword : Role, USAID, conservation.